MRSA colonization in workers from different occupational environments - Oliveira, Ketlyn (2022)
Funding: This research was supported by Instituto Politécnico de Lisboa, Lisbon, Portugal, by funding the Projects “Occupational exposure of ambulance drivers to bioburden” (IPL/2020/BIOAmbuDrivers_ESTeSL) and “Bacterial Bioburden assessment in the context of occupational exposure and animal health of swine productions” (IPL/2016/BBIOR-Health).